2020
DOI: 10.3390/ijms22010356
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Renin–Angiotensin–Aldosterone System in Dystrophin-Deficient Cardiomyopathy

Abstract: Dystrophin-deficient cardiomyopathy (DDC) is currently the leading cause of death in patients with dystrophinopathies. Targeting myocardial fibrosis (MF) has become a major therapeutic goal in order to prevent the occurrence of DDC. We aimed to review and summarize the current evidence about the role of the renin–angiotensin–aldosterone system (RAAS) in the development and perpetuation of MF in DCC. We conducted a comprehensive search of peer-reviewed English literature on PubMed about this subject. We found i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 203 publications
0
5
0
Order By: Relevance
“…Expression of ERRFI1 190 , ALOX12 191 , SOCS5 192 , DDIT4 193 , DUSP4 194 , IL6ST 195 , DUSP1 196 , SMAD1 197 , NCL (nucleolin) 198 , METTL14 199 , FMOD (fibromodulin) 200 , CYGB (cytoglobin) 201 , UNC5A 202 and TAAR9 203 are believed to be associated with diabetic nephropathy. Genes include FAP (fibroblast activation protein alpha) 204 , EYA4 205 , BCL9 206 , IRF2BP2 207 , EGR3 208 , GADD45B 209 , DMD (dystrophin) 210 , LSR (lipolysis stimulated lipoprotein receptor) 211 , DLL4 212 , SUN2 213 , SOS1 214 , PIK3CA 215 , GAMT (guanidinoacetate N -methyltransferase) 216 , RBM47 217 , HSP90AA1 218 , GAB1 219 , S1PR1 220 , EDNRB (endothelin receptor type B) 221 , NFKBIA (NFKB inhibitor alpha) 222 , GJA1 223 , GADD45G 224 , PHLDA1 225 , CMPK2 226 , FIGN (fidgetin, microtubule severing factor) 227 , KCNJ2 228 , ABCC9 229 , DIRAS3 230 , EPHX1 231 , RAB4A 232 , UBIAD1 233 , CASQ2 234 , TTN (titin) 235 , KCNH1 236 , JPH2 237 , OXGR1 238 , UCHL1 239 , SERPINA3 240 , MMP28 241 , ADAMTS2 242 , P2RY1 243 , CSF2RA 244 , MYO1F …”
Section: Discussionmentioning
confidence: 99%
“…Expression of ERRFI1 190 , ALOX12 191 , SOCS5 192 , DDIT4 193 , DUSP4 194 , IL6ST 195 , DUSP1 196 , SMAD1 197 , NCL (nucleolin) 198 , METTL14 199 , FMOD (fibromodulin) 200 , CYGB (cytoglobin) 201 , UNC5A 202 and TAAR9 203 are believed to be associated with diabetic nephropathy. Genes include FAP (fibroblast activation protein alpha) 204 , EYA4 205 , BCL9 206 , IRF2BP2 207 , EGR3 208 , GADD45B 209 , DMD (dystrophin) 210 , LSR (lipolysis stimulated lipoprotein receptor) 211 , DLL4 212 , SUN2 213 , SOS1 214 , PIK3CA 215 , GAMT (guanidinoacetate N -methyltransferase) 216 , RBM47 217 , HSP90AA1 218 , GAB1 219 , S1PR1 220 , EDNRB (endothelin receptor type B) 221 , NFKBIA (NFKB inhibitor alpha) 222 , GJA1 223 , GADD45G 224 , PHLDA1 225 , CMPK2 226 , FIGN (fidgetin, microtubule severing factor) 227 , KCNJ2 228 , ABCC9 229 , DIRAS3 230 , EPHX1 231 , RAB4A 232 , UBIAD1 233 , CASQ2 234 , TTN (titin) 235 , KCNH1 236 , JPH2 237 , OXGR1 238 , UCHL1 239 , SERPINA3 240 , MMP28 241 , ADAMTS2 242 , P2RY1 243 , CSF2RA 244 , MYO1F …”
Section: Discussionmentioning
confidence: 99%
“…Substantial amounts of renin released in the cardiac microenvironment upon cardiac mast cell degranulation [ 65 ] result in both AT-II formation within striking distance of AT1 receptor-expressing cardiac sympathetic nerve terminals and enhanced NE release ( Figure 1 ) and arrhythmias ( Figure 4 ) [ 171 , 172 ]. The fact that these events can be prevented by mast cell-stabilizing agents confirms the central role of cardiac mast cell-derived renin in AT1 receptor signaling [ 65 ].…”
Section: The Role Of Immune Cells In Cardiac Hypertrophymentioning
confidence: 99%
“…Yang et al found that the expression levels of vimentin and α -smooth muscle actin increased in human lung epithelial cells under mechanical ventilation injury [ 35 ]. Dystrophin is a large protein in which mutations can result in progressive muscle weakness, respiratory distress, and cardiovascular disorder [ 36 38 ]. It attaches the extracellular matrix to the cytoskeleton through F-actin and participates in events of signaling and synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%